5PSQ-032 Pharmacist integration in the multidisciplinary emergency team. Issue 1 (23rd March 2023) - Martinez, E; Corredor, I; Tardaguila, P; Dean, C; Casarrubios, GI; Miranda, A; Codonal, A; Horta, AM
Abstract : Background and Importance: Hospital pharmacists' activity is turning towards the direct care on clinical units. In Emergency Department (ED), medication errors (ME) may occur due to multiple factors: lack of coordination between services or pressure in medical care. Numerous studies, highlight the benefit of pharmacist intervention in the multidisciplinary health team. Aim and Objectives: The aim of this study was to analyse pharmaceutical interventions (PIs) carried out in ED, studied the ATC group of drugs involved and evaluate medical acceptance. Material and Methods: This two month (April-May 2022) prospective study was carried out in the Half-Stay Unit (HSU) of the ED in a second level hospital. Inclusion criteria: age ≥ 65 years and polypharmacy (≥ 5 drugs in chronic treatment). Variables collected: demographic, PIs, cause of PIs, medical acceptance and ATC group of drugs involved. Daily list of patients was obtained through the electronic prescription program and PIs were notified on-site or using this program. PIs were classified according to the system of the Consensus of Granada modified in drug discontinuation (unnecessary/duplicity/contraindication/interaction), drug change (contraindication/interaction), change of dose, frequency or schedule, initiation of treatment (usual treatment not prescribed/need additional treatment), monitoring (determination of plasma drug levels and follow-up) and prescription errors. PIs were considered accepted when doctor modified treatment in medical order or discharge report. Results: Final analyses included 52 patients. Median age was 82 years (IQR: 68-88), 58% men. During the study period, 120 PIs were performed and the 77% were accepted. 46% of PIs corresponded to initiation of treatment (usual treatment not prescribed), 15% to discontinuation (unnecessary drug), 15% to change in dosage, frequency or schedule, 14% to prescription errors and 10% others. ATC groups most frequently involved were C group (cardiovascular system) (35%) B group (blood and blood forming organs) (25%) and N group (nervous system) (20%). Conclusion and Relevance: Most of PIs corresponded to initiation of usual non-prescribed treatment followed by discontinuation of unnecessary drugs. Medical acceptance was high: Highlight PIs carried out around group C (lipid-lowering and antihypertensive drugs). Multidisciplinary team helps improve pharmacotherapeutic profile and patient safety. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.